Sacred Stones and Social Identity: The Cultural Persistence and Transformation of Precious Stone Traditions in Biringala Village, South Sulawesi - Rusdi Rusdi; Helmi Ayuradi Miharja; Humaira Ainun Adila (The Innovation of Social Studies Journal, 2025)
This study explores the enduring symbolic and cultural roles of precious stones in Biringala Village, South Sulawesi, Indonesia, where stones such as jade and agate function as ritual tools, social markers, and spiritual artifacts. Rooted in a broader anthropological inquiry into material culture and cultural resilience, the research investigates how these traditions persist, transform, or decline under the pressures of modernization and commodification. Drawing on a symbolic ethnographic approach, the study utilizes qualitative methods including semi-structured interviews, participatory observation, and documentation involving ritual leaders, elders, and community members. Thematic analysis reveals that while sacred stones continue to play a vital role in rituals such as Panrita, Assuro Maca, and Appassili, their meanings are increasingly contested among younger generations who perceive them more as aesthetic objects or commercial goods. The study also identifies strategies of cultural resilience through intergenerational knowledge transfer, local education initiatives, and cautious engagement with cultural tourism. Findings underscore how material symbols maintain their relevance not solely through static preservation but through adaptive practices negotiated within changing socio-cultural ecologies. The research concludes that despite the commodification and gradual desacralization of these stones, local actors in Biringala actively reshape their significance, suggesting a dynamic rather than static understanding of heritage. This study contributes to the anthropology of ritual and identity by illustrating how tangible cultural objects mediate between ancestral values and contemporary challenges, and highlights the importance of local agency in sustaining intangible cultural traditions through material expression.